2020
DOI: 10.1029/2019jc015879
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Low‐Mode Internal Tide and Its Interaction With Mesoscale Flow South of the Azores

Abstract: The breaking of internal waves results in diapycnal mixing which plays an important role in different climate relevant processes such as the transport of heat, freshwater, nutrients, pollutants, and dissolved gases. Thus, it is necessary to study the physics that drives diapycnal mixing to adequately represent the ocean's role in the climate system and to construct realistic climate models. Approximately 2 TW are needed to maintain the abyssal stratification of which internal tides contribute the main share, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
(156 reference statements)
1
14
0
Order By: Relevance
“…Kerry et al (2014) demonstrated that the location of eddies influenced the spatial pattern of IT propagation near the Luzon Strait. Löb et al (2020) observed a decrease in the energy flux of internal tides by approximately one-third when eddies interacted with internal tides; a decrease in the coherent part of the energy flux in the first two modes supported the hypothesis that wave-eddy interactions increased the incoherent part of the energy flux and transferred energy from low modes into higher modes, consequently leading to increased local dissipation. Huang et al (2018) showed a variety of mode-1 SIT modulations by an anticyclonic eddy and cyclonic eddy pair in the northern South China Sea, such as variations in the propagation speed of mode-1 SIT, leading to wave crest rotations and energy refraction, and an intensified mode-2 SIT was said to be transferred from mode-1 SIT through eddy-wave interactions.…”
Section: Introductionsupporting
confidence: 57%
“…Kerry et al (2014) demonstrated that the location of eddies influenced the spatial pattern of IT propagation near the Luzon Strait. Löb et al (2020) observed a decrease in the energy flux of internal tides by approximately one-third when eddies interacted with internal tides; a decrease in the coherent part of the energy flux in the first two modes supported the hypothesis that wave-eddy interactions increased the incoherent part of the energy flux and transferred energy from low modes into higher modes, consequently leading to increased local dissipation. Huang et al (2018) showed a variety of mode-1 SIT modulations by an anticyclonic eddy and cyclonic eddy pair in the northern South China Sea, such as variations in the propagation speed of mode-1 SIT, leading to wave crest rotations and energy refraction, and an intensified mode-2 SIT was said to be transferred from mode-1 SIT through eddy-wave interactions.…”
Section: Introductionsupporting
confidence: 57%
“…As low-mode ITs propagate through the ocean, the background mesoscale eddy field can modulate, inhomogenize and scatter the waves. This process by which a tidal wave field can become incoherent due to scattering by balanced flow and the energetics associated with the process has been investigated based on in situ measurements, satellite altimeter datasets and numerical simulations [98,99,[102][103][104][105][106][107][108][109]. These studies reveal that only a small fraction of low mode tidal energy, typically less than 5% wave energy, is lost to higher baroclinic wave modes in the low Rossby number regime as the wave propagates O(100-1000) km.…”
Section: (A) Low Mode Internal Tidesmentioning
confidence: 99%
“…[44,117,[144][145][146]182]. Furthermore, some features of wave-balance interactions, such as trapping of NIWs in anticyclonic mesoscale eddies [132,[134][135][136] and scattering and loss of coherence of ITs by mesoscale eddies [98,99,102,104,106,107] can be obtained from observational datasets. Theoretical and numerical investigations can choose relevant regimes based on observations and can cross check their results qualitatively with some selected features observed in the ocean.…”
Section: Challenges In Quantifying Wave-balance Energy Exchanges From...mentioning
confidence: 99%
“…The inclusion of internal tides dramatically increases the high‐frequency variability, particularly in the equatorial region. The increase is quite large off the Amazon shelf (near the equator), where internal tides are generated off the shelf break and propagate northeast and eastward into the open ocean (Jackson, 2004, 2007; Magalhaes et al., 2016), and around several bathymetry features/hot spots of the eastern North Atlantic basin, that is, the Sierra Leone Rise (∼5°N), the Cape Verde islands (∼15°N, Ray & Zaron, 2016), and the Atlantis‐Meteor Seamount Complex/Azores islands (30–36°N) (Löb et al., 2020; Zhao et al., 2016). The variability is also increased in the western boundary current around the New England seamounts chain (NESC).…”
Section: Surface Signature Of High‐frequency Motionsmentioning
confidence: 99%
“…The variability is generally weak in the equatorial region, although still noticeably higher than that in the low-EKE region such as the eastern North Atlantic Ocean (Figures 2a and 2b). (Jackson, 2004(Jackson, , 2007Magalhaes et al, 2016), and around several bathymetry features/hot spots of the eastern North Atlantic basin, that is, the Sierra Leone Rise (∼5°N), the Cape Verde islands (∼15°N, Ray & Zaron, 2016), and the Atlantis-Meteor Seamount Complex/Azores islands (30-36°N) (Löb et al, 2020;Zhao et al, 2016). The variability is also increased in the western boundary current around the New England seamounts chain (NESC).…”
Section: Surface Signature Of High-frequency Motionsmentioning
confidence: 99%